Panic Attack during Elective Gastrointestinal Endoscopy - Mitsonis, Charalampos (Hindawi Publishing Corporation, 2011)
Background. Esophagogastroduodenoscopy (EGD) and colonoscopy (CS) can evoke anxiety, embarrassment, and discomfort. These concerns can culminate in panic attacks, which may traumatize patients and significantly decrease their compliance to the procedure. The objective of this study was to evaluate the relationship between preendoscopic anxiety and the possibility of a panic attack during an elective gastrointestinal endoscopy (EGE). Methods. The study population comprised of 79 Greek outpatients. The examination was carried out without the use of conscious sedation. Patients' anxiety levels were assessed before the procedure using the Greek version of the Spielberger State-Trait Anxiety Inventory (STAI-Y). Results. Seventy-nine patients were enrolled: 45 EGD and 34 CS. Females had higher state and trait anxiety levels than males (48.14 ± 7.94 versus 44.17 ± 7.43, P < 0.05; and 43.68 ± 6.95 versus 39.86 ± 7.46, P < 0.05). Patients who experienced panic attack had significantly higher levels of both trait and state anxiety, compared to those who were panic-free. There was no significant relationship between panic attacks and sex or type of procedure. Conclusions. Patients who experience panic attacks during endoscopic procedures appear to have significantly higher anxiety levels before the procedure. Administering the STAI questionnaire prior to the endoscopy seems to be a useful screening method for vulnerable patients.